Efektivitas Manajemen Risiko Dan Manajemen Proses Dalam Pencegahan Fraud di Divisi YAN HC PT. PLN UID Jatim - Al Abid, Muhammad Lailul Muzakky; Purwanto, Sugeng (Jurnal Christian Humaniora, 2024)
In today's era, we face various risks, such as fraud in various sectors, ranging from economic, social, political, environmental, business decisions and the insurance sector. The existence of this risk is closely related to how it is managed, which is an integral part of the organization both on a sectoral and universal scale. According to the report "A Report To The Nations" in 2022, Indonesia had 23 cases of fraud and was the fourth country with the most fraud cases after Australia, China, and Malaysia. All of these events encourage a focus on more intensive risk recovery and control. In other words, operational risk management methods and their impacts are becoming increasingly relevant. Including at PT PLN UID Jawa Timur, namely the YAN HC Surabaya division which is responsible for managing employee health insurance data. The raw data from this process is carefully processed to be accurate and support decision making, especially on the PLN FIT Website platform, which monitors health transactions between the company and the First Level Health Facilities (FKTP) in East Java. The management of this health data faces the risk of data fraud, which can occur due to misuse of internal or external data. This risk has a major impact on the credibility, employee performance, and company finances. YAN HC Surabaya Division implements risk management strategies to identify, measure, and control risks to prevent fraud. Risk management is not only to reduce losses, but also to prepare the organization to face any risks that may occur. This risk management is an early detection tool that helps prevent anomalies in data from collection to presentation on the PLN FIT Website, by involving continuous monitoring and comprehensive analysis of data flow. In addition to technology, this data management also relies on the implementation of strict Standard Operating Procedures (SOP). Yan HC Surabaya Division ensures that every data process follows the rules set to maintain accuracy and validity. Strict supervision and control are carried out in inputting raw data into the PLN FIT Website, and this SOP is an important step to prevent errors that can lead to fraud. This study uses a library research method with a qualitative approach, which highlights the importance of the role of risk management and performance management in overcoming possible fraud. The risk management program aims to increase confidence in the company's financial reporting and reduce audit risk. Basically, risk management is a solution to dealing with the risk of fraud. This study also aims to discuss fraud detection through anti-fraud strategies